Les liens entre les questions sur le quatrième livre des Sentences de Pierre Lombard rédigées à prague (par l’auteur de l’Utrum Deus gloriosus), Leipzig (par un élève de Jean de Monsterberg) et Cracovie (par Matthias de Sąspów) au xve siècle - Baran, Wojciech (Acta Mediaevalia. Series Nova, 2024)
The research carried out in this article shows that the manuscript Kraków, AiBKKK, Ms 113 uses the questions to Book IV of the Sentences composed by the student John of Monsterberg in Leipzig in 1409–1415, also conserved in the manuscript Kraków, BJ, 1721. Six of the fifty–seven questions contain similarities with the Utrum Deus gloriosus. This fact testifies to the reception of theological ideas known in Prague in the fifteenth century, not only in Kraków but also in Leipzig. Forty questions from this commentary were used by Matthias of Sąspów, a scholar from Kraków, without major changes, which confirms Matthias’ depen- dence on the Leipzig questions, already noted by Zofia Włodek.